2009
DOI: 10.1002/jgm.1314
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of small interference RNA‐mediated gynaecophoral canal protein silencing in Schistosoma japonicum

Abstract: Background Schistosomiasis causes liver and intestinal damage and can be very debilitating. The pairing of a male worm with a female worm residing in the gynaecophoral canal of male plays a critical role in the development of female parasite. Because the male specific gynaecophoral canal protein of Schistosoma japonicum (SjGCP) is found in significant quantities in the adult female worm after pairing, it could play an important role in parasite pairing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
1
41
1
Order By: Relevance
“…Therefore, our results implied that the SjIAP could be functionally involved in apoptosis regulation in S. japonicum. Although direct evidences were not presented in the study to document the SjIAP partner and/or their interactions, future studies will be warranted to elucidate their roles by using RNA interference in combination with GST pull-down technique or yeast two-hybrid system (Cheng et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…Therefore, our results implied that the SjIAP could be functionally involved in apoptosis regulation in S. japonicum. Although direct evidences were not presented in the study to document the SjIAP partner and/or their interactions, future studies will be warranted to elucidate their roles by using RNA interference in combination with GST pull-down technique or yeast two-hybrid system (Cheng et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…The landmark availability of the complete sequences of the S. japonicum (171) and S. mansoni (18) genomes will provide the necessary ancillary information. As well, new approaches in antigen discovery through the generation of a large schistosome transcriptome database, gene finding, and the explosion in postgenome technologies, including DNA microarray profiling, proteomics, glycomics, immunomics, and the application of RNA interference (RNAi) and novel imaging techniques (2,24,25,41,53,72,73,75,76,85,95,109,126,127,179,189,197,205,219,224,230), provide an unprecedented opportunity to identify a new generation of vaccine target molecules that may induce greater potency than the current candidate schistosome antigens (138).…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…Since discovery of the first miRNA (lin-4) in 1993 by Lee (Lee et al 1993) and RNA interference in 1998 by Andrew Fire (Fire et al 1998) in Caenorhabditis elegans, three different kinds of snRNAs, including small interfering RNAs (siRNAs), microRNAs (miRNAs), and piRNA (Piwi-interacting RNA), have been widely investigated in many organisms. In S. japonicum, it had been well established for a while that the usages of siRNAs were able to artificially induce specific endogenous mRNA degradation at transcript level (Cheng et al 2005b;Cheng et al 2009). Very recently, a considerable number of miRNAs have also been identified in different development stages of schistosomes and further studies indicated that the expression profiles of these miRNAs were associated with parasite development, suggesting that miRNAs could be involved in regulating schistosome development Hao et al 2010;Wang et al 2010).…”
Section: Introductionmentioning
confidence: 98%